Postcolonialism and the Hebrew Bible : the next step - Boer, Roland, 1961- (Semeia studies, 2013)
This volume returns to where initial interest in postcolonial biblical criticism began: the Hebrew Bible. It does so not to celebrate the significant achievements of postcolonial analysis over the last few decades but to ask what the next step might be. In these essays, established and newer scholars, many from the interstices of global scholarship, discuss specific texts, neo/post/colonial situations, and theoretical issues. Moving from the Caribbean to Greenland, from Ezra-Nehemiah to the Gibeonites, this collection seeks out new territory, new questions, and possibly some new answers. The contributors are Roland Boer, Steed Davidson, Richard Horsley, Uriah Y. Kim, Judith McKinlay, Johnny Miles, Althea Spencer-Miller, Leo Perdue, Christina Petterson, Joerg Rieger, and Gerald West. --